1990
DOI: 10.1148/radiology.176.1.2353114
|View full text |Cite
|
Sign up to set email alerts
|

Safe use of an intravenous power injector for CT: experience and protocol.

Abstract: Use of a power injector to deliver contrast material intravenously for computed tomography is a safe alternative to a bolus or drip infusion technique. The authors performed 5,280 injections at rates of 0.5-5.0 mL/sec. Six extravasations occurred, and none resulted in long-term sequelae. This complication rate is 0.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 0 publications
1
27
2
2
Order By: Relevance
“…In spite of the radiologist's efforts to prevent CMEV, it continues to occur in every CT room. In most practices, the reported frequency is less than 1% [3,4,7] . Since the replacement of MI by API, the number of reported CMEV incidents has increased but the relation between CMEV and injection rate remained controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the radiologist's efforts to prevent CMEV, it continues to occur in every CT room. In most practices, the reported frequency is less than 1% [3,4,7] . Since the replacement of MI by API, the number of reported CMEV incidents has increased but the relation between CMEV and injection rate remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The automatic power injector (API) enables CM to be delivered as a nonfragmented bolus at a high fl ow rate, which is essential for many HCT protocols [3,4] such as CT angiography and multiphasic organ imaging. Although the number of reported extravasations has increased since APIs were introduced in CT scanning, the relationship between the frequency of contrast media extravasation (CMEV) to the injection rate remains debatable [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…al. [1] as well as Miles et al [17]. Over 90% of patients in both groups in which symptoms of acute post-contrast allergic reaction were reported, had received Ultravist 370 through an automatic syringe, a manual syringe having been used in only three of them.…”
Section: Discussionmentioning
confidence: 97%
“…More side effects were reported by patients who received iopromid with an automatic syringe than by those to whom doctors administered it manually. Both Kopp et al [1] and Miles et al [17] suggested that extravasations which can lead to local inflammatory reactions are more common on automatic than in manual injection. This was not confirmed by Jacobs et.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of a power-assisted injection over manual injection or drip infusion has been demonstrated [1,2] and is widely accepted. Particularly in spiral CT where the amount of contrast material, time of injection, and scan delay represent crucial factors and are part of standarized protocols, the advantage of power injecting is self-evident.…”
Section: Introductionmentioning
confidence: 99%